ELECTRONIC MOISTURE SENSOR CALIBRATION IN DIFFERENT SOIL TEXTURES - Gava, R.; da Silva, E. E.; Baio, F.H.R. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The accuracy of the humidity sensor readings depends on the device's quality, but also its calibration. These electronic sensors have been factory calibrated, however, it is known that this varies with the type of soil. The objective of this study was to calibrate the sensor Falker, Hidrofarm model in soil sandy and clay texture. PVC columns were used to 0.1m diameter and 0.3m height, which inserted in the soil after saturated, allowed collecting soil samples without disaggregation thereof. In the laboratory, each column received a probe of the equipment. After the samples are saturated, began the natural drying process, kept in the laboratory with constant temperature and humidity made frequent measures. Where did readings with the device, the columns were too heavy for determination of moisture in mass. So with the soil density obtained by relating between the mass and volume of the column, were found soil moisture and correlate with the instrument readings. Correlation curves were fitted between the readings obtained by the sensors and the respective humidity measures. The sensor reading deviation to the real measure moisture presented to be systematic, being -8% for the clayey soil and -4% for the sandy soil.